Analysis of oxygen consumption rates in zebrafish reveals differences based on sex, age and physical activity recovery - Konadu, Bridget; Hosler, Jonathan P.; Gibert, Yann; Edwards, Kristin S. (Frontiers in Physiology, 2023)
Introduction: Mitochondrial dysfunction is linked to a variety of human diseases. Understanding the dynamic alterations in mitochondrial respiration at various stages of development is important to our understanding of disease progression. Zebrafish provide a system for investigating mitochondrial function and alterations during different life stages. The purpose of this study was to investigate our ability to measure mitochondrial oxygen consumption rates in zebrafish embryos, larvae, and adults as an indicator of mitochondrial function.Methods: Basal respiration of entire zebrafish embryos (5 dpf), larvae (0.6-0.9 cm), young adults (3-month-old), and old adults (12-month-old) was measured using an Oroboros Oxygraph, with a stirrer speed of 26 rpm. For embryos and larvae, 'leak' respiration (plus oligomycin), maximum respiration (plus uncoupler), non-mitochondrial respiration (plus inhibitors), and complex IV activity were also measured. To induce physical activity in adult fish, the stirrer speed was increased to 200 rpm.We demonstrate the ability to accurately measure respiration rates in zebrafish at various ages using the Oroboros Oxygraph. When comparing zebrafish embryos to larvae, embryos have a higher maximum respiration. Three-month-old zebrafish males have higher basal respiration than females, while 12-month-old zebrafish females exhibit greater rates of respiration than males and younger females. When the stirrer speed was increased, respiration rates decrease, but with differences depending on sex. This study demonstrates a simple and accessible method to assess zebrafish physiology by mitochondrial oxygen consumption measurements in an unmodified Oroboros Oxygraph. The method should facilitate studies to understand the intricate interplay between mitochondrial function, development, and aging.